Solvability of the system of linear inequalities - Vilkas, E. (Lithuanian Mathematical Journal, 1966)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Э. И. Вилкас. Разрешимость системы линейных неравенств E. Vilkas, Tiesinių nelygybių sistemos išsprendžiamumas